Course design aspects of blended learning in undergraduate education - Sanjeewanie Hemamali Dias Senanayake; Thanuja Chandani Sandanayake (International Journal of Evaluation and Research in Education (IJERE), 2024)
Blended learning is a popular teaching mode in today’s higher education system. Course design for blended education presents a challenge for educational specialists. This research aims to identify the essential aspects of course design in undergraduate blended learning. Course content, course structure and delivery, collaborative engagement, learner facilitation, and assessment and evaluation were discovered as aspects of blended learning course design. Based on the identified aspects, a survey questionnaire was designed and pilot tested to check the reliability and validity of the measurement tool. The analysis revealed that the questionnaire was acceptable in terms of psychometric characteristics after removing four items. Therefore, 23 items remained in the final questionnaire, which was considered reliable and valid for the context. The information was gathered using an online questionnaire from academic staff at Sri Lankan state universities attached to the departments conducting degree programs in the computing discipline. There were 97 participants included in the final dataset. The results were analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The results revealed that ‘assessment and evaluation’ was highly considered when designing undergraduate blended learning courses, while other aspects which are also imperative, have been paid less attention by the university academicians.